THE ROLE OF HEALTH EDUCATION IN THE PREVENTION AND MANAGEMENT OF HYPERTENSION IN THE ELDERLY: A LITERATURE REVIEW - Wati, Nenden Lesmana; Raningg, Putri; Rochman, Dadang (Journal of Nursing Culture and Technology, 2025)
Introduction: Hypertension is a significant health problem that, if not properly managed, can lead to more severe complications. Hypertension requires proper and accurate treatment. Systolic blood pressure over 140 mmHg and diastolic blood pressure over 90 mmHg is known as hypertension. Objective: To understand the role of health education in the prevention and management of hypertension in the elderly. Methods : The method used in this study is a literature review. Academic articles were searched through online databases such as PubMed and Google Scholar from 2019-2024, resulting in 10 relevant articles. Results : Based on the review and analysis of the 10 selected articles, it was concluded that education can increase respondents' knowledge regarding the prevention and management of hypertension. Conclusion : The role of nurses in assisting patients can improve health by providing information about the care and medical treatments they receive, and by offering nursing care to meet the needs of hypertensive patients and provide the necessary treatment.